Hubungan Self Regulated Learning terhadap Prestasi Akademik Mahasiswa Semester Satu Tahun Ajaran 2021/2022 Fakultas Kedokteran Universitas Pattimura - Cindy L. Ririhena; Johan B. Bension; Ony W. Angkejaya (Journal on Education, 2023)
Academic achievement is a benchmark for achieving learning outcomes in tertiary institutions which are education providers at an advanced level of secondary education. Academic achievement in medical students is measured by using the Achievement Index (GP) obtained from the accumulation of blocks. In undergoing education at the medical faculty, students must be able to regulate self-regulation in learning well, because students must be more independent and active in the learning process. The purpose of this study was to determine the relationship between self-regulated learning and academic achievement of first semester students of the 2021/2022 academic year, Faculty of Medicine, University of Pattimura. The method used in this research is analytic with a cross-sectional research design using a Self-Regulated Learning questionnaire. The results of the the study on 201 respondents stated that 49.8% had a high level of self-regulated learning and 95% of the respondents had achieved good academic achievement. Data analysis was performed using the Chi-Square test. The results of the analysis showed that 98% of students with high SRL had satisfactory academic achievement and 2% were unsatisfactory, 91.6% of students with moderate SRL achieved satisfactory academic achievement and 8.4% were unsatisfactory, 5% of students with SRL low achieve satisfactory academic achievement and 16.7% unsatisfactory. The results of the significance of p = 0.068, so it can be concluded that self-regulated learning does not have a significant relationship with academic achievement